Tari Nusantara Sebagai Pengayaan Wawasan Sosial Budaya Bagi Siswa Di SMA Negeri 2 Kota Pariaman - Siti Aisyah Jasmin; Indrayuda Indrayuda (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
This article aims to describe and reveal the role of Indonesian dance as an enrichment of Indonesian knowledge for students at SMA Negeri 2 Kota Pariaman. This type of research is qualitative research using the demonstration method. The instrument for this research is the researcher himself and is assisted by supporting instruments such as writing equipment and a camera. Data was collected through observation, interviews, literature study and documentation. Data was analyzed using the stages of data collection, data reduction, data display and data verification. The results of the research show that the implementation of Indonesian dance training at SMA 2 Pariaman has been running in accordance with the achievement indicators of extra-curricular activities, namely building knowledge and insight as well as dance skills with an Indonesian perspective. The impact of the Nusantara dance training at SMA 2 Pariaman is that students' insight into the Archipelago increases in terms of knowing and understanding cultural identity and cultural aspects attached to the Nusantara dance being trained. Students can understand the Archipelago insight from the aspects of movement, music, costumes and dance procedures or the dance style of the dance.